Skinning with dual quaternions - O'SULLIVAN, CAROL ANN (My University, 2007)
Skinning of skeletally deformable models is extensively used for real-time animation of characters, creatures and similar objects. The standard solution, linear blend skinning, has some serious drawbacks that require artist intervention. Therefore, a number of alternatives have been proposed in recent years. All of them successfully combat some of the artifacts, but none challenge the simplicity and efficiency of linear blend skinning. As a result, linear blend skinning is still the number one choice for the majority of developers. In this paper, we present a novel GPU-friendly skinning algorithm based on dual quaternions. We show that this approach solves the artifacts of linear blend skinning at minimal additional cost. Upgrading an existing animation system (e.g., in a videogame) from linear to dual quaternion skinning is very easy and has negligible impact on run-time performance.
PUBLISHED
Keywords: skinning; rigid transformations; blending; dual quaternions; linear combinations